Fumigant activity of three aromatic essential oils against fruit fly Bactrocera carambolae - Rini Pujiarti; Ananto Triyogo; Suputa Suputa; Brandon Aristo Verick Purba (Universitas Lampung, 2026)
Essential oils have attracted considerable attention as environmentally friendly alternatives to synthetic insecticides because of their selective neurotoxicity, high volatility, and rapid biodegradability. This study investigated the chemical composition and fumigant toxicity of the essential oils of Melaleuca cajuputi, Amomum cardamomum, and Myristica fragrans against the fruit fly Bactrocera carambolae. The chemical constituents of each oil were characterized by gas chromatography–mass spectrometry (GC–MS), and their fumigant toxicity was evaluated by determining the median lethal concentration (LC50) and 90% lethal concentration (LC90). GC–MS analysis identified 27 compounds in M. cajuputi oil, with 1,8-cineole (34.88%), α-terpineol (10.52%), β-caryophyllene (10.44%), α-humulene (5.74%), and limonene (5.15%) as the major constituents. A. cardamomum oil contained 32 compounds and was dominated by 1,8-cineole (60.48%), followed by β-pinene (8.24%) and α-terpineol (5.35%). In contrast, M. fragrans oil contained 12 compounds, with sabinene (21.51%), α-pinene (17.34%), terpinen-4-ol (15.92%), β-pinene (15.10%), β-phellandrene (8.72%), and α-terpinene (5.95%) as the principal constituents. Among the three oils, M. fragrans exhibited the highest fumigant toxicity against B. carambolae, with LC50 and LC90 values of 0.05 and 0.48 μL/L, respectively, followed by M. cajuputi (LC50 = 0.82 μL/L; LC90 = 1.48 μL/L) and A. cardamomum (LC50 = 2.58 μL/L; LC90 = 3.43 μL/L). The superior fumigant toxicity of M. fragrans was associated with its characteristic mixture of monoterpene hydrocarbons and oxygenated monoterpenes, whereas the high proportion of 1,8-cineole in A. cardamomum alone did not result in greater toxicity. These findings demonstrate that M. fragrans essential oil is a promising botanical fumigant for the management of B. carambolae and highlight the importance of overall chemical composition rather than the abundance of a single constituent in determining fumigant efficacy.